2018
DOI: 10.1002/cae.22056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of competence acquisition in a flipped classroom approach

Abstract: Higher Education Institutions are interested in describing qualifications in terms of competences and abilities that prepare graduates best for their future professional and social life. This study aims to analyze students’ acquisition of competences, on one hand, inside the classroom using a flipped learning approach, on the other hand, outside the classroom through students’ self‐study using information and communication technology resources such as teaching videos, virtual labs, simulations, or game‐based l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 55 publications
0
16
0
2
Order By: Relevance
“…For this practice lesson, the fourth one, we found that the flipped classroom concept could be useful to save time [2,8,12,19]. A global approach to the problem can be found in References [1,6,7] with more general recommendations and good practices when it comes to conducting learning research techniques.…”
Section: Methodsmentioning
confidence: 99%
“…For this practice lesson, the fourth one, we found that the flipped classroom concept could be useful to save time [2,8,12,19]. A global approach to the problem can be found in References [1,6,7] with more general recommendations and good practices when it comes to conducting learning research techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The Learning Management Systems Modular Object-Oriented Dynamic Learning Environment (LMS MOODLE) system is an open education information learning environment. This environment is able to integrate various informational training systems across the university, department, specialty, and a consortium of universities [84]. In the universities of the Russian Federation, LMS MOODLE is widely used, and its use does not require any special knowledge and skills from the user [85].…”
Section: Methodsmentioning
confidence: 99%
“…This is an example of meaningful gamification [26], a new approach to the concept of gamification that puts greater focus on user-based experience and engagement beyond simple game mechanics. Similarly, Hung [27] ran a study on the positive impact of a digitally-enhanced board game with QR codes and gamified quizzes to test the preparation of the students at the beginning of each class, and research carried by Estriegana et al [28] presented the dual integration of gamification for pre-class preparation and in-glass GBL activities.…”
Section: Serious Games In the Fcmentioning
confidence: 99%